Pengembangan LKPD Terintegrasi Etnosains Batik Semarang untuk Meningkatkan Literasi Kimia Siswa - Fitri Siami; Woro Sumarni; Sudarmin Sudarmin; Harjono Harjono (Postgraduate, University of Mataram, 2023)
The problem of this research is developments in the 21st century that require someone to have special abilities, namely chemical literacy. This is in accordance with the 2013 curriculum which demands responsiveness to developments in science, culture, technology, and the arts. The aim of this research is to develop worksheets and improve students' chemical literacy skills in acid-base material. The method used uses a research and development approach with a research flow that adopts the 4-D development model, i.e. definition, design, development, and dissemination. However, this research was carried out up to the 3-D stage, i.e. definition, design, and development. The feasibility of the LKPD is seen through the assessment of material expert validators at 92.86% and media validators at 96.67% in the